Lack of effect of aspirin in asymptomatic patients with carotid bruits and substantial carotid narrowing. The Asymptomatic Cervical Bruit Study Group. - Côté, R; Battista, R; Abrahamowicz, M; Langlois, Y; Bourque, F; Mackey, A (1995)
OBJECTIVE: To determine the effectiveness of aspirin in preventing ischemic events in patients with asymptomatic carotid stenosis. DESIGN: Double-blind, placebo-controlled trial. SETTING: University-affiliated hospitals. PATIENTS: 372 neurologically asymptomatic patients with carotid stenosis of 50% or more in at least one artery as determined by luminal diameter reduction on duplex ultrasonography. INTERVENTION: Patients were randomly assigned to receive either enteric coated aspirin, 325 mg/d, or identically appearing placebo. Duration of therapy was 2.0 years for the aspirin recipients and 1.9 years for the placebo recipients. OUTCOME MEASURES: Patients were scheduled for a clinical examination every 6 months for assessment of the occurrence of any clinical event in the composite end point, which consisted of transient ischemic attack, stroke, myocardial infarction, unstable angina, or death. RESULTS: At baseline, the 188 patients receiving aspirin and the 184 patients receiving placebo had similar demographic, ultrasonographic, and laboratory characteristics. The median duration of follow-up was 2.3 years. The annual rate of all ischemic events and death from any cause was 12.3% for the placebo group and 11.0% for the aspirin group (P = 0.61). The Cox proportional hazards analysis yielded an adjusted hazard ratio (aspirin-placebo) of 0.99 (95% CI, 0.67 to 1.46; P = 0.95). The annual rates for vascular events only were 11% for the placebo group and 10.7% for the aspirin group (P = 0.99). The multivariate analysis yielded a hazard ratio of 1.08 (CI, 0.72 to 1.62; P = 0.71). CONCLUSION: Aspirin did not have a significant long-term protective effect in asymptomatic patients with high-grade (> or = 50%) carotid stenosis.